Renaissance Dam and Development in Ethiopia: National Gains and Regional Losses - Wso, Aram A.; Elmourad, Nagla Elmourad Abdullh (European Scientific Journal, ESJ, 2026)
This article examines the Grand Ethiopian Renaissance Dam (GERD) project and its impact on the development of Ethiopia on the one hand, and the downstream countries, Egypt and Sudan, on the other. It highlights the economic, political, and social gains Ethiopia has achieved through the construction of the dam, as opposed to the losses incurred by Egypt and Sudan in these areas. The article also discusses regional challenges related to water management and presents models of successful co-operation, such as the Mekong River experience and the 1995 agreement that established a joint committee to manage the basin. The article proposes a set of solutions to achieve joint development among the three countries, based on regional cooperation, the establishment of a tripartite committee to manage the river’s resources, and the adoption of water and non-water projects that benefit all parties. The article concludes by emphasising the importance of establishing a common institutional framework that ensures the fair and sustainable use of the Nile’s waters, thereby promoting regional stability and development.